Weeds. Season two [videorecording (DVD)] - Kohan, Jenji, 1969- (Lionsgate, 2007)
Nancy Botwin is a soccer mom who had to learn how to deal - pot, that is - after the death of her husband. Now, her business is a hit. But keeping up with the neighbors in this suburban utopia isn't easy. She is joined up with a few of her closest friends, and together they face life's ups and downs - because even in paradise, nobody's perfect.